Effects of transesterification and degradation on properties and structure of polycaprolactone–polylactide copolymers - Lipik, Vitali T.; Widjaja, Leonardus K.; Liow, Sing S.; Abadie, Marc J.M.; Venkatraman, Subramanian S. (Polymer degradation and stability, 2010)
Ester bonds of biodegradable polymers, such as poly (α-hydroxy esters), synthesized by the coordinated anionic ring opening polymerization (CAROP), are subject to transesterification during synthesis. In this work, a series of poly(ɛ-caprolactone)-poly( l-lactide) (PCL-PLA) block and random copolymers with targeted molar mass of 10,000 Da was synthesized to study the mechanism of transesterification reactions via NMR and MALDI-TOF. Polylactide segments are more vulnerable to transesterification compared to polycaprolactone. As a result, the actual quantity of l-lactide in the polymers was less than the target for all studied copolymers because of the decarboxylation and consequent CO elimination from fragments of macromolecules after transesterification. The presence of decarboxylation during transesterification was confirmed analytically and was reflected in the MALDI-TOF and 13C NMR spectra. An analysis of the polymer structure pointed to dehydration reactions that led to the formation of cyclic structures and double bonds with possible crosslinking.